Uji Beberapa Konsentrasi Bakteri Bacillus sp. Endofit untuk Meningkatkan Pertumbuhan Bibit Kakao (Theobroma cacao L.) - Puspita, Fifi; Saputra, Sukemi Indra; Merini, dan Jenny (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
Development of cocoa (Theobroma cacao L.) requires high-quality seeds. Adding growth substance from Bacillus sp. endophytes is expected to increase the growth of cocoa seedlings. The purpose of this research was to evaluate the ability of Bacillus sp. endophytes to produce Indole Acetic Acid (IAA) hormone, evaluate the effects of Bacillus sp. endophytes application on growth of cocoa seedling, and obtain the best concentration to increase growth of cocoa seedling. The experiments were conducted in the laboratory and in the field from June to October 2015. The study was conducted in two stages: in vitro and in vivo.The first experiment tested the ability of Bacillus sp. endophytes to produce IAA using tryptophan enriched picovskaya liquid medium and non-enriched tryptophan. The results from the first experiment showed that all Bacillus sp. endophytes produce IAA hormones. The second experiment tested the concentrations of Bacillus sp. endophytes to improve the growth of cocoa seedlings. The experiment was conducted using a completely randomized design consisting of 5 treatments and 4 replications, i.e., without treatment of Bacillus sp., and concentrations of 1011, 1012, 1013, and 1014 cfu/mL. The parameters observed were the number of bacterial colonies of Bacillus sp. endophytes, cocoa seed height, stem diameter, number of leaves and planting area of 4 month cocoa seedlings. The results from the second experiment showed that all concentrations of Bacillus sp. endophytes increase the growth of cocoa seedlings. The concentration of 1011 cfu/mL produced more colony in planting medium, increased height, stem diameter, leaf number and leaf area in cocoa seedlings.